Breast cancer stigma among Indonesian women: a case study of breast cancer patients - Solikhah Solikhah; Ratu Matahari; Fitriana Putri Utami; Lina Handayani; Tri Ani Marwati (BMC, 2020)
Abstract Background The stigma experienced by cancer patients stems from the association of cancer with death, as cancer is the most feared disease worldwide, especially among cancer patients and their families. The stigma regarding breast cancer screening behaviour has not been critically evaluated and is poorly understood; therefore, we aimed to analyse the stigmatization of breast cancer patients in Indonesia to reduce the morbidity and mortality of breast cancer. Methods A qualitative study using a focus group discussion (FGD) and in-depth interviews with thematic analysis was conducted. Results One informant experienced breast pain and kept the referral letter, in which the medical doctor advised medical treatment, to herself for 3 months due to her embarrassment. A traditional healing practice known as 'kerokan', which involves scraping of the skin, and consumption of a traditional drink were used by most informants to decrease their breast pain. Finally, most informants were diagnosed with an advanced stage of cancer when they returned to the health care facility. In addition, financial difficulties were noted as barriers to breast cancer screening in Indonesia. Conclusions Feelings of fear and shame when diagnosed with breast cancer were reported by the informants in this study. Alternative treatment known as 'kerokan' was the first treatment sought for breast cancer symptoms due to financial difficulties among breast cancer patients. Informants were diagnosed with an advanced stage of cancer after they returned to the health care facility. A better understanding of early breast cancer symptoms could motivate women to seek out breast cancer treatment.